Peningkatan Berkelanjutan dalam Pengelolaan Limbah Medis Padat COVID-19 Di Fasilitas Pelayanan Kesehatan : Systematic Review - Ardhini Nugrahaeni; Wachyu Sulistiadi (Jurnal Dunia Kesmas, 2022)
AbstractHealth care facilities need to improve services continuously by implementing a Quality Management System, namely ISO 9000: 2015. ISO 9000: 2015 in its implementation is continuous quality improvement (CQI). Success in implementing this quality standard through continuous improvement can provide customer satisfaction and improve service performance. In an effort to improve quality, it is necessary to have quality indicators. One of the quality indicators is the management of solid medical waste(SMW) in accordance with regulations. During the COVID-19 pandemic, the number of cases increased resulting in the accumulation of solid medical waste to increase. Objective: to improve the management of COVID-19 SMW in health facilities. Method: PRISMA. This method is used to evaluate the management of COVID-19 SMW in health facilities so that new innovations are found. Barriers in Indonesia and abroad are the lack of infrastructure, knowledge, funds, storage, transportation, monitoring and evaluation. The buildup of COVID-19 SMW results in the transmission of the COVID-19 virus, so efforts are needed to improve it. The implementation requires top management commitment and is communicated and documented. Furthermore, supervision, monitored  and evaluated. Barriers related to lack of facilities and knowledge of officers. Improvement efforts require commitment from top management. The recommendations provided are energy recovery facilities, Build-Operate-Transfer-Agreement, Electronic Scheduled Waste, complaint services, coaching clinic, and pyrolysisKeywords: continuous improvement, quality indicators, solid medical waste